Dark ages : the case for a science of human behavior - McIntyre, Lee C. (MIT Press, 2006)
Why the prejudice against adopting a scientific attitude in the social sciences is creating a new "Dark Ages" and preventing us from solving the perennial problems of crime, war, and poverty.